Pengaruh Padat Penebaran Terhadap Kelulushidupan Dan Pertumbuhan Udang Vanname(Litopenaeus vannamei) Serta Produksi Biomassa Rumput Laut (Gracilaria sp.) PADA Budidaya Polikultur - Putri, Yulina Sulistiani; Susilowati, Susilowati (Journal of Aquaculture Management and Technology, 2013)
This research aimed to determine the effects of stocking density of vanname and Gracilaria sp. and the interaction between the stocking density of vanname shrimp and Gracilaria sp, the survival rate and growth of vanname shrimp, as well as biomass production of Gracilaria sp. in polyculture. This research was carred out at Coastal Area Development Laboratory (LPWP) Jepara from July-September 2012. A factorial design was applied in this experiment. There were two factors applied i.e. factor A: the stocking density of the shrimp, factor B: the stocking density of Gracilaria sp. action A consisted of 2 levels: A1 (14 shrimp/m2), A2 (17shrimp/m2). Where as factor B consisted of 3 levels: B1 ( 33,75 g/bag), B2 ( 40 g/bag), B3 ( 56,25 g/bag), Each treatment was replicated three times. The results of this research showed there was can interaction the stocking density of vanname shrimp and Gracilaria sp., ther were interaction between the stocking density of shrimp and Gracilaria sp., and showed a highly significant effect on their growth rate. The results of the growth rates 4,26Â±0,11 %/day in both treatment A2B2 (stocking density of 17 vanname shrimp /bag, and Gracilaria sp. 40 g/bag). The results biomass production of seaweed 3,69 Â±0,11 g in both teatment A1B1 (stocking density of 14 vanname shrimp/bag, and Gracilaria sp. 40 g/bag).